ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN TAHUNAN - Sundari, Siti (Journal of Accounting and Strategic Finance, 2009)
This research is aimed to examine the influence of financial variables as liquidity ratio, leverage ratio, profitability ratio and public share on the full disclosure in annual report in Mining companies listed in Indonesian Stock Exchange.Twelve companies participated in this study and the samples for this research are ten companies listed in Indonesian Stock Exchange from 2004-2006. Data were collected by means of purposive sampling. The analytical methods used are those of multiple regession analysis. The hypotheses tested that liquidity ratio, leverage ratio, profitability ratio and public share significantly influence on the full disclosure in annual report. The result  of the multiple regression analysis for influence of financial variables on the full disclosure in annual report show that leverage ratio and pubic share significantly influences on the full disclosure in annual report. Whereas Liquidity ratio and profitability ratio do not significantly influence on the full disclosure in annual report. Keywords:  Liquidity Ratio, Leverage Ratio, Profitability Ratio, Public Share and the Full Disclosure in Annual Report